2015
DOI: 10.4269/ajtmh.14-0212
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Management of Dysglycemia in Children in the Developing World

Abstract: Abstract. Improving the availability of point-of-care (POC) diagnostics for glucose is crucial in resource-constrained settings (RCS). Both hypo and hyperglycemia have an appreciable frequency in the tropics and have been associated with increased risk of deaths in pediatrics units. However, causes of dysglycemia, including hyperglycemia, are numerous and insufficiently documented in RCS. Effective glycemic control with glucose infusion and/or intensive insulin therapy can improve clinical outcomes in western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Both hypo and hyperglycemia occur frequently in sick children and have been associated with increased risk of deaths in pediatrics units [ 1 , 2 ]. Neonates and young children are particularly susceptible to hypoglycemia leading to the well recognized long term sequelae especially with prolonged fasting [ 3 – 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both hypo and hyperglycemia occur frequently in sick children and have been associated with increased risk of deaths in pediatrics units [ 1 , 2 ]. Neonates and young children are particularly susceptible to hypoglycemia leading to the well recognized long term sequelae especially with prolonged fasting [ 3 – 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Young children have a limited tolerance for fasting [ 1 ]. Hypoglycemia in non-neonate children is independently associated with poor outcomes in the tropics [ 13 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to identify hypoglycaemia is not sufficient if the appropriate therapy remains unavailable [23], and this may be a more pronounced problem in lower-level facilities that lack intravenous infusions. When there are complete stock-outs of dextrose infusions, health workers reported that they dissolve sugar in water and give it to the child orally.…”
Section: Discussionmentioning
confidence: 99%